ANALISIS PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL, TERHADAP ETIKA AKUNTANSI - Helda Marlin Ala (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2018)
This study aims to analyze the influence of intelligence quotient of accounting ethics in accounting students sector public econimic faculty at the UKAW Kupang, the emotional quotient  of spiritual  quotient of accounting ethics in accounting students sector public econimic faculty at the UKAW Kupang, the influence of spiritual  quotient of accounting ethics in accounting students sector public econimic faculty at the UKAW Kupang, and the influence of intelligence quotient, emotional quotient, and spiritual quotient simultaneosly on the accounting ethics in accounting students sector public econimic faculty at the UKAW Kupang. The focus variables of research are intelligence quotient, spiritual  quotient, spiritual  quotient as independentvariables about accounting ethics as a bound variable.The results of this study can be seen that intelligence quotient and emotional quotient does significantly impact to accounting ethics, and spiritual  quotient does significantly impact the accounting ethics. Keywords: Intelligence Quotient, Emotional Quotient, Spiritual  Quotient, and Accounting Ethics.